Distance education in higher education in the context of reclusion as a human education policy in Portugal - Moreira, José António; Machado, Ana; Trindade, Sara Dias (Education Policy Analysis Archives, 2018)
Higher Education in Portugal has undergone massive changes due to information and communication technologies (ICT) advancements and changes resulting from the Bologna Process, by which learning should be accessible for all regardless of social exclusion reasons, such as imprisonment. The aim of this paper is to understand the viewpoints of fifteen respondents (students and senior rehabilitation technicians) concerning the quality of pedagogical processes in Distance Learning in a Portuguese prison. This study occurs in a context of a non-positivist paradigm, placing the emphasis on the perception of individuals through a qualitative methodology. The results obtained from interviews show that the education process has many weaknesses and limitations, with respect to its organization, evaluation, resources available and hourly availability. The conclusion is that it is essential to provide better conditions for prisoners to receive this type of education, as it can be an opportunity for obtaining professional qualification and for personal development, thus increasing their prospects of success in the future.